Recent progress in piezoelectric thin films as self-powered devices: material and application - Song, Zhiqiang; Hou, Rongxi; Jiang, Feng (Frontiers in Materials, 2024)
Piezoelectric materials have become a key component in sensors and actuators in many industrial fields, such as energy harvesting devices, self-powered structures, biomedical devices, nondestructive testing, owing to the novel properties including high piezoelectric coefficient and electromechanical coupling factors. Piezoelectric thin films integrated on silicon substrates are widely investigated for their high performance and low manufacturing costs to meet the requirement of sensor networks in internet of things (IoT). The aim of this work is to clarify the application and design structure of various piezoelectric thin films types, synthesis methods, and device processes. Based on latest literature, the process of fabricating thin film sensors is outlined, followed by a concise overview of techniques used in microelectromechanical systems (MEMS) processing that can integrate more complex functions to obtain relevant information in surrounding environment. Additionally, by addressing piezoelectric thin films sensors as a cutting-edge technology with the ability to produce self-powered electronic devices, this work delivers incisive conclusions on all aspects of piezoelectric sensor related features. A greater understanding of piezoelectricity is necessary regarding the future development and industry challenges.